Process design of ITM oxidation pond and packaged plant / Ruslan Hassan - Hassan, Ruslan (1991)
There are several methods used In the design of biological wastewater treatment plants. These include empirical, pilot plants studies and actual field performance. This work concentrates on field data by studying the performance of ITM Oxidation Pond and ITM Packaged Treatment Plant. Field samples were taken by composite sampling technique. Several kinetic parameters were obtained. These are the Monod parameters, Ks and Um needed in the formulation for the process design. The simulation made use of Biotreat program.